Quantification of Ecoservices in Traditional Agroforestry Systems in Semi Arid Tropics (Bangladesh Journal of Botany, 2021)
Neem (Azadirachta indica A. Juss.) being an important tropical tree, traditional neem-based agroforestry (bund/boundary/scattered tree planting with field crops) systems were evaluated for their carbon sequestration (CS) potential, soil quality, pest dynamics and provisioning services in comparison with prevailing grain based system in the tropical India. Results revealed higher economic gain from soil quality services followed by CS in all the agroforestry systems among the non-marketable services, whereas higher provisioning services were obtained with crops alone. In all, total economic value was higher in boundary planting ($ 1053.94/ha/yr) followed by bund planting ($ 961.95/ha/yr) and was lower with scattered planting ($ 939.76/ha/yr). However, the provisioning services ($ 841 - 889/ha/yr) rendered by agroforestry systems were lower than those of agriculture alone ($ 904/ha/yr) but were still significant from ecological and sustainable angles.Bangladesh J. Bot. 50(2): 427-432, 2021 (June)